2016
DOI: 10.1155/2016/9468193
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Curcumin in Treatment of Spinal Cord Injury

Abstract: Current treatment for spinal cord injury (SCI) is supportive at best; despite great efforts, the lack of better treatment solutions looms large on neurological science and medicine. Curcumin, the active ingredient in turmeric, a spice known for its medicinal and anti-inflammatory properties, has been validated to harbor immense effects for a multitude of inflammatory-based diseases. However, to date there has not been a review on curcumin's effects on SCI. Herein, we systematically review all known data on thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 57 publications
(54 reference statements)
0
13
1
Order By: Relevance
“…Although previous studies have reported that curcumin is a neuroprotective agent and might improve motor function [10,17], we did not find any significant impact of nanocurcumin on functional measures. One reason for this finding could be the relatively progressed disease in most of the included patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Although previous studies have reported that curcumin is a neuroprotective agent and might improve motor function [10,17], we did not find any significant impact of nanocurcumin on functional measures. One reason for this finding could be the relatively progressed disease in most of the included patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Curcumin also protects axons from NO-mediated destruction (Tegenge et al, 2014[ 44 ]). A recent study has shown that NPCs combined with curcumin can downgrade the severity of spinal cord injury by affecting the metabolism of prostaglandin, thromboxane, NO, leukotriene, cyclooxygenase and peroxidase (Sanivarapu et al, 2016[ 39 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Some considerations have been raised about the current curcumin research. First, it has been demonstrated that curcumin can cross the blood–brain barrier [43], and percolate into the cerebrospinal fluid (CSF) [49]. The CSF can circulate in the subarachnoid space around the brain and spinal cord, which achieves the delivery of curcumin to the spinal cord.…”
Section: Discussionmentioning
confidence: 99%